Climate Risk Adaptation Analysis and Prospect of New Power System - ZHANG Haonan, CUI Limin (Dianli jianshe)
In recent years， the world has suffered many major power safety incidents caused by extreme weather events that have severely impacted economic and social development and global energy transition. Considering the development strategy of China’s new power system and the realistic problem of frequent extreme weather events and climate risks， we analyzed the correlation between the new power system and climate， and expound the broad connotation of "adaptability" based on the concepts of "resilience"， "flexibility"， "reliability"， and "stability" to describe the level of power system safety. We thus established a framework for analyzing the climate adaptability of the new power system and explored the key issues and strategies for enhancing the climate adaptability of the new power system. Furthermore， we delved into the research direction of high-quality development of the new power system from the perspective of climate risk adaptability to enrich the theoretical study of the new power system within the framework of a climate-resilient society.